PENGARUH SUASANA TOKO, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA BERUNDING COFFEE YOGYAKARTA - Handoko, Jonathan Lukas (PERFORMA, 2023)
Some recent years, Indonesians have experienced quite significant increase of coffee consumption. World Coffee Organization states that the increase of coffee consumption occurs as 44% in recent ten years, while Global Agricultural Information Network predicts that national coffee consumption keeps on increasing with the range of 13,9% per year. That opportunity is used by Berunding Coffee’s owner as the reason to open the first coffee shop in August 2020. Based on its name, Berunding Coffee places service value as main thing that has to be own by coffee shops and that thing can be started with "negotiation" activities between barista and the customers. Along its way, Berunding Coffee finds some obstacles, one of them is store atmosphere that becomes the main obstacle in achieving customer satisfaction. The purpose of this research is to find the influence of store atmosphere, service quality, and price perception on customer satisfaction of Berunding Coffee Yogyakarta. Data collection in this research is done by distributing online Likert scale questionnaires through google form to 159 respondents who have visited and consumed Berunding Coffee products previously. The sample that is taken by using purposive sampling method. All data that is obtained will then be processed and analyzed using Statistical Product and Service Solution (SPSS) Version 17 software. From multiple regression test that has been done, it is obtained that the result of store atmosphere has significant value of 0.003 < 0.05, service quality has significant value of 0.00 < 0.05, and price perception has significant value of 0.00 < 0.05, which means that the store atmosphere, service quality, and price perception influence significant on customer satisfaction. Those three independent variables also simultaneously influence significant on customer satisfaction or dependent variable.